A Two-Phase Infinite/Finite Low-Level Memory Model: Reconciling Integer–Pointer Casts, Finite Space, and undef at the LLVM IR Level of Abstraction - Beck, Calvin; Yoon, Irene; Chen, Hanxi; Zakowski, Yannick; Zdancewic, Steve (Proceedings of ACM on programming languages, 2024)
This paper provides a novel approach to reconciling complex low-level memory model features, such as pointer--integer casts, with desired refinements that are needed to justify the correctness of program transformations. The idea is to use a "two-phase" memory model, one with an unbounded memory and corresponding unbounded integer type, and one with a finite memory; the connection between the two levels is made explicit by a notion of refinement that handles out-of-memory behaviors. This approach allows for more optimizations to be performed and establishes a clear boundary between the idealized semantics of a program and the implementation of that program on finite hardware. The two-phase memory model has been incorporated into an LLVM IR semantics, demonstrating its utility in practice in the context of a low-level language with features like undef and bitcast. This yields infinite and finite memory versions of the language semantics that are proven to be in refinement with respect to out-of-memory behaviors. Each semantics is accompanied by a verified executable reference interpreter. The semantics justify optimizations, such as dead-alloca-elimination, that were previously impossible or difficult to prove correct.